Toward Reform: Revamping Family Law in Muslim Nations - Kartini, Aisyah; Sulfinadia, Hamda; Efrinaldi (Maqasid: Jurnal Studi Hukum Islam, 2024)
This research explains in more detail about family law reform in several Muslim-majority countries such as Indonesia, Malaysia, Brunei, Turkey, Egypt, Jordan, Morocco, Syria and other countries. The purpose of this article is to provide a small overview of how reforms are taking place in the field of family law in several Muslim countries. Problems that arise in family law have three important components, namely marriage, divorce and inheritance. This discussion will reveal the results of reforms or changes that arose as a result of shifts in era and power from the colonial period to the period of independence. As technology develops and new problems arise, Muslim countries also provide regulations in several ways so as to produce compatibility between law and society. This research uses a normative research type, a literature study with a descriptive analysis research type. The method is carried out by combining several descriptions of changes or reforms that occurred in the formulation of Family Law Laws in Muslim Countries so as to obtain the desired results. Laws that are in line with current developments will be very much needed, especially in the field of family law. then returning laws that deviate from the teachings that are applied is a denial.